SERANGGA-SERANGGA BERKEMAMPUAN MERUSAK PADA TANAMAN PEKARANGAN DI TELUKNAGA, CITEUREUP DAN PACET - ATMOWIDJOJO, A.H.; ADISOEMARTO, S.; AMIR, M. (Research Center for Biology-Indonesian Institute of Sciences, 1985)
ANITA H. ATMOWIDJOJO, S. ADISOEMARTO & M. AMIR. 1985. Potential insect pests on vegetations of home gardens in Teluknaga, Citeureup and Pacet. Berita Biologi 3 (2) : 55 - 65. A total of 60 species of insects were recorded associated with 78 species of plants in three research localities. However, not all of these species were distributed equally, either in space or time. Many were found specific on certain host plants for the localities. On the other hand, there were host plants that harboured specific insect pests. It was also found that the seriousness of damage was not related to the specificity (in either way). A serious pest on certain host was not necessarily a serious pest on other host plants.